Lighting a Fire: Gasdermin-Mediated Pyroptosis Remodels the Glioma Microenvironment and Promotes Immune Checkpoint Blockade Response - Cai, Yonghua; Li, Ke; Lin, Jie; Liang, Xianqiu; Xu, Wei; Zhan, Zhengming; Xue, Shuaishuai; Zeng, Yu; Chai, Peng; Mao, Yangqi; Song, Zibin; Han, Lei; et al. (Frontiers in Immunology, 2022)
Pyroptosis is a proinflammatory programmed cell death pathway mediated by gasdermins. Exploring the role of pyroptosis can provide new insights into tumor malignancy. The most recent studies on pyroptosis have focused on tumor cells. However, the effects of pyroptosis on the tumor microenvironment (TME), immunotherapeutic responses, and efficacy have been neglected, especially in case of glioma. In this study, four independent glioma cohorts comprising 1,339 samples and a pan-cancer cohort comprising 10,535 tumor samples were analyzed. The relationships among pyroptosis status, prognosis, microenvironment cellular components, and clinical and biological phenotypes were investigated through the identification of pyroptosis subtypes, construction of a gasdermin-related prognostic index (GPI), and evaluation of immunological characteristics in glioma. The Genomics of Drug Sensitivity in Cancer database and “pRRophetic” package in R were used to estimate temozolomide (TMZ) sensitivity. The “Submap” package and external immunotherapy cohorts were used to investigate and confirm the role of GPI in response to and efficacy of immunotherapy in glioma. Finally, potential small-molecule compounds related to GPI were identified using the connectivity map database and mode-of-action analysis. We identified three different pyroptosis subtypes: cluster 1 (C1) characterized by a higher GPI, while cluster 2 (C2) and cluster 3 (C3) characterized by a lower GPI. The high GPI of C1 was associated with glioma progression and worse prognoses, whereas the low GPI of subtype C2 and C3 was associated with better prognoses. However, patients with high GPIs were found to be more sensitive to TMZ and immune checkpoint blockade than those with low GPIs. Furthermore, gasdermin D may be a principal potential biomarker and play key roles in pyroptosis-inducible therapy combined with immunotherapy in glioma. This study provides a clinical, biological, and molecular landscape of pyroptosis and suggests that pyroptosis of glioma cells may perform the dual function of promoting both tumorigenesis and antitumor immunity.